A functional role for the middle extracellular region of the neural cell adhesion molecule (NCAM) in axonal fasciculation and orientation - Pollerberg, G. Elizabeth; Beck-Sickinger, Annette (Developmental biology, 2002)
A new monoclonal antibody (mAb HR1) was used to study the function of a previously neglected region in the extracellular domain of the neural cell adhesion molecule (NCAM). Application of mAb HR1 in retina organ culture interferes with several axonal functions in the developing eye. The antibody disturbs the orientation of axons growing in the peripheral retina and the tracking of axons in the middle retina. In the central retina, fasciculation is disturbed and a proportion of the ganglion cell axons do not leave the eye at the optic fissure but are misrouted to the contralateral side of the retina. Analysis of peptide fragments of NCAM indicates that the epitope of mAb HR1 resides in the region C-terminal to the fifth immunoglobulin (Ig) domain. Moreover, mAb HR1 binds to the oligopeptide comprising the 15 amino acids immediately C-terminal to the fifth Ig domain of NCAM. In addition, binding of mAb HR1 to NCAM is increased by removal of the large polysialic acid chains of the fifth Ig domain. Taken together, the data show that this region of NCAM—which has been previously reported to represent the flexible hinge region of the molecule—is crucial for the function of this molecule, in particular on cell surfaces in motion, e.g., those of growing axons in the developing nervous system.